INTRODUCTION OF THE EDUCATIONAL AND INFORMATION ENVIRONMENT "VIRTUAL CABINET OF PHYSICS" IN THE EDUCATIONAL PROCESS OF PHYSICS OF THE INSTITUTION OF LEVEL II - Банак, Роман (SWorldJournal, 2020)
Today, the teacher is the organizer of active cognitive activity of students, so it is necessary to modernize forms of learning, to include in the practice of teaching such ways of student activity that would create conditions for the development of his p